2006
DOI: 10.1097/01.gme.0000196594.82452.83
|View full text |Cite
|
Sign up to set email alerts
|

The relation of season of birth to severity of menopausal symptoms

Abstract: In this study, we found a relationship between season of birth and some menopause-associated symptoms. Further study is needed to confirm these relationships and examine possible mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Research suggests an increased prevalence of emotional behavioral disorders, including broader internalizing problems (Greer, 2005; Polizzi, Martin, & Dombrowski, 2007), as well as behavioral inhibition (a predictor of anxiety; Gortmaker, Kagan, Caspi, & Silva, 1997) and specific anxiety symptoms (Greer, 2005; Parker & Neilson, 1976) associated with spring births. Fetal central nervous system development is thought to be negatively affected due to the increase in influenza and maternal ill health during winter months, when mothers of spring babies are pregnant (Cagnacci, Pansini, Bacchi-Modena, Volpe, & Emilia-Romagna Operative Group for Menopause, 2006; Laplante, Brunet, & King, 2016). While both explanations are plausible, direct assessment of maternal ill health, and the mechanisms that may be involved in the transmission of exposure to a disaster (i.e., maternal/fetal blood and placentas) resulting in specific anxiety symptoms, are needed to clarify our finding.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests an increased prevalence of emotional behavioral disorders, including broader internalizing problems (Greer, 2005; Polizzi, Martin, & Dombrowski, 2007), as well as behavioral inhibition (a predictor of anxiety; Gortmaker, Kagan, Caspi, & Silva, 1997) and specific anxiety symptoms (Greer, 2005; Parker & Neilson, 1976) associated with spring births. Fetal central nervous system development is thought to be negatively affected due to the increase in influenza and maternal ill health during winter months, when mothers of spring babies are pregnant (Cagnacci, Pansini, Bacchi-Modena, Volpe, & Emilia-Romagna Operative Group for Menopause, 2006; Laplante, Brunet, & King, 2016). While both explanations are plausible, direct assessment of maternal ill health, and the mechanisms that may be involved in the transmission of exposure to a disaster (i.e., maternal/fetal blood and placentas) resulting in specific anxiety symptoms, are needed to clarify our finding.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a large body of research outside of economics has proven that season of birth is associated with health outcomes such as developing schizophrenia (Watson et al, 1984;Torrey et al, 1997;Davies et al, 2003;and Tochigi et al, 2004), autism (Gillberg, 1990), dyslexia (Livingston et al, 1993), severity of menopausal symptoms (Cagnacci et al, 2006), extreme shyness (Gortmaker et al, 1997), risk for suicide (Rock et al, 2006) and life expectancy among the elderly (Costa and Lahey, 2005;and Doblhammer et al, 2005). Research has even suggested an association between season of birth and self-reported "luckiness" (Chotai and Wiseman, 2005) and season of birth and the likelihood of being left-handed (Martin and Jones, 1999).…”
Section: Season Of Birth and Later Outcomesmentioning
confidence: 99%
“…A study on modern Italian women described that menopause-associated symptoms were highest in women born in June and lowest after birth in November [41]. German girls born in August were reported to experience menarche four months later than those born in October [37], supporting the finding of a later age at menarche in South African girls born in late summer and early autumn [36].…”
Section: Season Of Birth Effects On Reproduction In Womenmentioning
confidence: 81%
“…A variety of studies provide evidence that seasonal factors present during fetal or early postnatal reproductive development might affect reproductive characteristics later in life, such as fertility [29][30][31][32], offspring count [33][34][35], reproductive lifespan [34], birth seasonality of the offspring [29,33], age at menarche [36,37], seasonality of menarche [38], timing of menopause [39,40], menopause-associated symptoms [41], menstrual disorders [39], twinning rate [42,43], birth weight [44,45], and sex ratio of the offspring [46,47].…”
Section: Season Of Birth Effects On Reproduction In Womenmentioning
confidence: 99%